REVITALIZING THE EDUCATIONAL LANDSCAPE POST-PANDEMIC: AN IN-DEPTH ANALYSIS OF CHALLENGES AND ISSUES IN TEACHING AND LEARNING - Irma Wani Othman; Frederick Chong Chen Tshung; Syahrul Nizam Salam; Mohd Kamal Mohd Shah; Saifulazry Mokhtar; Muhammad Safuan Yusoff (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study focuses on teaching and learning (T&L) comprehension, examining the impact of the COVID-19 pandemic on education. Due to the pandemic, especially COVID-19, the study analyzes online sources, identifying significant impacts, such as the shift to online T&L during the Movement Control Order (PKP) enforced by the Malaysian Ministry of Education (KPM) and Ministry of Higher Education (KPT). Post-pandemic, the study explores knowledge dissemination methods in educational institutions following the termination of movement control orders in early 2022. This paper addresses several issues, including (i) educational institution preparedness to facilitate the T&L process, (ii) the role of face-to-face education in nurturing students’ soft skills, (iii) the recovery of the teaching and learning system post-pandemic, and (iv) the advantages and disadvantages of digital learning. The research findings reveal that efforts to restructure the handling of T&L have been carried out extensively, following the recommendations of the Ministry of Health Malaysia (MOH) at the national level and the World Health Organization (WHO) at the international level. Additionally, educational institutions at various levels have offered various educational alternatives and facilities to ensure the continuity of education and the production of high-quality graduates poised to contribute to various sectors with the potential to revitalize the nation’s economy post-Movement Control Order (PKP) since 2020. The research results indicate that in the post-pandemic era, face-to-face education is demanded by the community, as it is perceived as the most effective method for imparting knowledge and honing an individual’s soft skills. Recommendations focus on addressing student absenteeism during home-based T&L (PdPR) for post-pandemic T&L recovery, allowing students to revisit subjects as preparation for assessments. The Ministry of Education introduced online learning during the Movement Control Order (PKP), with an evaluation of digital media’s effectiveness and shortcomings. This evaluation is crucial for rapid improvements in the post-pandemic education system, assessing digital learning’s effectiveness as an alternative method.